Aproximações entre ética cristã e ética empresarial: apontamentos a partir do eixo da responsabilidade social - Soares, Lisandro Silveira (2015)
This final paper for the professional Master s program has as its goal to analyze the Christian Ethic and the Business Ethic seeking contributions for the elaboration of a possible Christian Business Ethic. The theme is very current and lacks foundation within standards which consider the issue of social responsibility in the theological area. The methodology used was bibliographic and conceptual research. The results of the research show up based on the consideration of social responsibility from the theological viewpoint and its possible tie to the business world. We conclude considering the possibility of an ethics incarnated in the bosom of business management and of the stakeholders, problematizing the various real difficulties and the normative complexities of an organization which prioritizes the logic of maximizing the profits. Within the distinction between morality and ethics, we fulfill the necessary contributions which permeate possible programs of Christian business ethics, laying out concrete issues such as equitable salary, participation in the decision making, encouragement for organization of play and the prioritization of human dignity.